CENOZOIC SEDIMENTATION HISTORY OF THE CONGO BASIN REVISITED - (:unkn) unknown (My University, 2016)
The Congo Basin in Central Africa is one of the major river basins of the world. Its history overthe last 75 Myr should record global and major regional events, including the Paleocene-EoceneThermal Maximum at ~55 Ma and the Miocene aperture of the Western branch of the EastAfrican Rift System along its eastern border at ~25 Ma. Available data for associated off-shoredeposits show that the Congo River delta experienced a starvation period during the MidtoLate Cretaceous and Paleogene, with endorheic lacustrine to desert environments in theupstream basin, followed by a period marked by high rates of drainage and sediment supplyin the Neogene.Here we complement this sedimentation history with a multi-proxy analysis of an on-shorePaleogene section along the west coast of Central Africa (Landana, Cabinda Enclave, Angola)and with new age determination results for paleosurface-related manganese oxide depositsfrom the southern margin of the Congo Basin in the DR Congo.Newly obtained 39Ar-40Ar ages for cryptomelane from Katanga (Kasekelesa) and Kasaï (MtMwatshimwa) reveal an old (Cretaceous?) surface that developed before ~76 Ma and they suggestthe existence of at least two younger Eocene denudation episodes, during the Lutetian(~45 Ma) and the Priabonian (~35 Ma). They furthermore confirm the identification of a seriesof Mio-Pliocene denudation surfaces that were previously recognized by the same methods forthe Kisenge area, Katanga (De Putter et al., 2015). It is likely that the newly obtained Cretaceousage records the subcontinental ‘African Surface’ that had previously not been identified forCentral Africa.The Landana section presents a condensed (~45 m) Paleogene-Neogene sequence. The Paleogenedeposits (~25 m), dated by the rich fossil assemblage they contain (Solé et al., in prep.),record a shallow marine carbonate environment with minor to moderate fine-grained terrigenousdetrital input. Sediment provenance, as documented by εNd, does not change
Keywords: African Research